Carl Claubergs metode for sterilisering uten operasjon - Knut Ruyter (Septentrio Academic Publishing, 2020)
The methods of Carl Clauberg for sterilization of women without surgery: A research ethics journey: from a new ethic for doctors and nurses via clinical research in Auschwitz to lawsuit in Schleswig During a recent visit to Auschwitz I was surprised to learn how little I knew about the clinical research done by professor Carl Clauberg and how scarce the references are in the education of health professionals and in the field of research ethics. Clauberg's research aimed at developing the most effective «methods and means» to make women permanently sterile. The method was to be the preferred procedure for mass sterilization of all women of inferior value, be they Jewish or Slavic or regarded as degenerate. The encounter with block 10 in Auschwitz was the start of a research ethics journey through archives in Auschwitz and Schleswig to see if there were any explanations to the evildoing of doctors and nurses and to the difficulties of prosecuting evil - it was also a reminder about how easy we can be influenced by external forces and what it takes to withstand them.